(untitled) - Agnes C Rola Zenaida S Provido (Los Bamos, Languna, Philippines, 1998)
The book describes a village-level study that measured the educational, economic, and efficiency impacts of the Farmer Field School (FFS). The ultimate aim is to improve farmers' decision-making abilities to cope biotic (insect pests, weeds) and abiotic (water, soil, weather) stresses
Keywords: agriculture - economic aspects